Deep Participation in Underserved Communities: A Quantitative Analysis of Hearken's Model for Engagement Journalism. (27th May 2020) - Brannock Cox, Jennifer; Poepsel, Mark A.
ABSTRACT: Hearken is a proprietary news engagement platform growing in popularity. Under the Hearken approach, audience members are invited to participate in the newsmaking process. Hearken strives to assist news organizations in providing local and hyperlocal content that meets audience needs and demands while preserving elements of the journalist's role as gatekeeper. Hearken has also worked to help news organizations reach underrepresented populations with mixed results per its own anecdotal analyses. This study employs a quantitative content analysis comparing one year's worth of coverage at four different local NPR affiliates in the United States to provide a breakdown of Hearken content versus traditional reporter-driven content in the following four categories: emphasis on hyperlocal coverage, story topic prevalence within local and hyperlocal coverage, emphasis on coverage of underrepresented communities, and story topic prevalence within coverage of underrepresented communities. Findings reveal listener-driven Hearken content favors hyperlocal news on lifestyle issues while reporter-driven stories emphasize state-level governance and politics as well as local crime. These indicate a stark contrast between the content audiences want and that which journalists tend to report. The nuanced normative implications, possibilities and limitations of Hearken's model of "deep participation" are addressed in some detail.